2009
DOI: 10.1159/000204765
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Profiles of Instrumental Activities of Daily Living in Different Subtypes of Mild Cognitive Impairment

Abstract: Background/Aims: The purposes of this study were to describe restrictions in instrumental activities of daily living (IADL) in mild cognitive impairment (MCI) and to assess different patterns of IADL in each MCI subtype. Methods: A total of 566 participants, those not cognitively impaired (NCI; n = 311) and MCI patients (n = 255), 60–94 years old (71.25 ± 6.00), were examined. Neuropsychological tests were administered to participants, and each MCI patient was classified into one of four subtypes. They complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
59
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 51 publications
(30 reference statements)
12
59
0
1
Order By: Relevance
“…One Korean study, using the Seoul IADL test, demonstrated that md-aMCI patients had impairment in the same IADL items, except medication [25]. Functional disabilities in our md-aMCI subjects also involved meal preparation, housework, and leisure.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…One Korean study, using the Seoul IADL test, demonstrated that md-aMCI patients had impairment in the same IADL items, except medication [25]. Functional disabilities in our md-aMCI subjects also involved meal preparation, housework, and leisure.…”
Section: Discussionmentioning
confidence: 82%
“…Subjects with isolated memory impairment were defined as sd-aMCI, and subjects with impairment of memory plus one or more other cognitive domain (scores greater than 1.0 SD below the scores of normal aged control subjects) were defined as md-aMCI. Executive impairment was defined as impairment on at least two of the VF, TMT-B, SCW, and DBS tests [25]. Language impairment was recognized by impairment in BNT, and visuospatial impairment was defined by impairment in a copy of CFT.…”
Section: Methodsmentioning
confidence: 99%
“…The association between cognitive impairment and dependence in IADL shows the importance of this aspect for performing activities that require a higher level of independence and autonomy. IADL variables, such as using the telephone, managing money and medication are tasks that require multiple cognitive functions such as memory and planning, making them more vulnerable to this commitment (26) . In another study, intellectual activity and social role, factors related to cognitive status were identified as predominant for functional decline in the IADL only (24) .…”
Section: Discussionmentioning
confidence: 99%
“…In general, persons with MCI report more difficulties than healthy elderly individuals with engaging in social conversation, telephone use, finding belongings, grocery shopping, driving, and medication management (Aretouli & Brandt, 2009; Muangpaisan, Assantachai, Intalapaporn, & Pisansalakij, 2008; Kim et al, 2009; Peres et al, 2006; Ryu, Ha, Park, Yu, & Livingston, 2010; Schmitter-Edgecombe, Woo, & Greeley, 2009; Wadley et al, 2008). Psychological well-being has been examined in four studies of people with MCI and has included measures of life satisfaction, mastery, affect, and social interaction (Ready, Ott, & Grace, 2004).…”
Section: Living With MCImentioning
confidence: 99%